Comparison study of different indoleamine-2, 3 dioxygenase inhibitors from the perspective of pharmacodynamic effects. (September 2020) - Jiang, Xue; Li, Xiaopeng; Zheng, Shuang; Du, Guangying; Ma, Jinbo; Zhang, Liming; Wang, Hongbo; Tian, Jingwei
Introduction: Indoleamine 2, 3-dioxygenase (IDO) was a potential tumor immunotherapy target. IDO inhibitors showed inconsistent results in clinical trials, but no preclinical comparative study was reported. The purpose of this study was to evaluate the differences of representative IDO inhibitors (PCC0208009, INCB024360, NLG919) from the pharmacological perspective. Methods: In vitro experiments included: inhibition effects on IDO activity in cell and enzyme-based assay, effects on IDO expression in HeLa cells, and enhancement of proliferation and activation of peripheral blood mononuclear cell (PBMC). In vivo experiments included: pharmacokinetics and tumor distribution in CT26-bearing mice, effects on Kyn/Trp and anti-tumor effect and immunological mechanism in CT26 and B16F10 tumor-bearing mice. Results: Compared with INCB024360 and NLG919, PCC0208009 effectively inhibited IDO activity at lower dose 2 nM and longer duration more than 72 h, had higher enhancements on PBMC proliferation and activation, and could inhibit the IDO expression in Hela cells. The pharmacokinetics characteristics of three IDO inhibitors were similar in CT26-bearing mice. In CT26 and B16F10 tumor-bearing mice, PCC0208009 and INCB024360 had similar effects in Kyn/Trp reduction, and more potent than NLG919; three IDO inhibitors had similar effects in tumor suppression, changes of the percentages of CD3 + CD8 + and CD3 + CD4 + T cells, and activation of tumor infiltrating lymphocytes, while PCC0208009 had a better tendency than INCB024360 and NLG919. Conclusion: PCC0208009, INCB024360, and NLG919 were all effective IDO inhibitors, but the comprehensive pharmacological activity of PCC0208009 was better than INCB024360 and NLG919, which was basically consistent with the results or progresses of clinical trials.